COMMODIFICATION OF REOG AND WAROK ARTS AS CULTURAL IDENTITY OF PONOROGO REGENCY - Rakhma Widya Dharojah; Nuril Endi Rahman; Malik Ibrahim (Yayasan Nusantara Hasana Berdikari, 2024)
The art of reog an warok in Ponorogo Regency is a community culture formed through a long historical process. Amid the onslaught of foreign cultures, reog Ponorogo still exists as an artistic tradition and is in demand by the community. Commodification is an unavoidable phenomenon in the era of globalization, where an object is converted into a selling value. Culture is inseparable from commodification, where economic value is the main attraction in commodification. This research aims to reveal and describe the various strategies of the commodification of reog and work arts in the Ponorogo Regency. The method used is descriptive qualitative. The research data collection used in-depth interview techniques, observation, and documentation studies. The research analysis was conducted inductively, and the data validity technique used source triangulation. The results of this study are, the art of reog Ponorogo has experienced commodification where the Ponorogo Regency government makes reog a symbol of tourism, which aims to present to source of regional income. Commodification and the existence of tradition in the art of reog Ponorogo can go hand in hand, despite the shift in orientation but reog art is still attached as the identity of the people of Ponorogo Regency.